Rats and leptospirosis, a unique tropical experience - Bahaman, Abdul Rani (Veterinary Association Malaysia, 2017)
Rats are the maintenance host for leptospirosis and are the source of the infection to humans and animals. To eradicate leptospirosis, then the maintenance hosts should be eliminated. This is not possible, particularly when it involved wildlife like rats. A good alternative then is to impose biological control on the rat population which is a safe and pragmatic approach. The environment is the indirect source of infection and in tropical countries; recreational areas are often the place foroutbreaks of leptospirosis. Claims that leptospires survive for months in the environment probably is not true. The “top up” or daily excretion of leptospires from the maintenance hosts particularly rats make it appears that the leptospires survived for months in the environment. The good news is that although there are many infected rats in the cities, there were hardly any reports of outbreaks of leptospirosis in urban areas. Outbreaks of leptospirosis tend to be in the countryside particularly in recreational areas, where infection is easily transmitted through the conjunctiva or mucous membrane of the upper respiratory or gastro-intestinal tract through water activities.